2013
DOI: 10.1007/s11356-013-1659-0
|View full text |Cite
|
Sign up to set email alerts
|

Using biochar for remediation of soils contaminated with heavy metals and organic pollutants

Abstract: Soil contamination with heavy metals and organic pollutants has increasingly become a serious global environmental issue in recent years. Considerable efforts have been made to remediate contaminated soils. Biochar has a large surface area, and high capacity to adsorb heavy metals and organic pollutants. Biochar can potentially be used to reduce the bioavailability and leachability of heavy metals and organic pollutants in soils through adsorption and other physicochemical reactions. Biochar is typically an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
257
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 734 publications
(271 citation statements)
references
References 77 publications
8
257
0
6
Order By: Relevance
“…Terra Petra) (Lehmann and Joseph, 2009). Moreover, Fellet et al (2011), Beesley and and Zhang et al (2013) demonstrated the effectiveness of biochar to remediate PTE contaminated mine soils by reducing their concentrations in soil pore water and in the plants grown in the amended soils.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Terra Petra) (Lehmann and Joseph, 2009). Moreover, Fellet et al (2011), Beesley and and Zhang et al (2013) demonstrated the effectiveness of biochar to remediate PTE contaminated mine soils by reducing their concentrations in soil pore water and in the plants grown in the amended soils.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Similarly, grain yield and biological yield increased for all application rates of RHC and RH compared to that of the control. The increase in the number of tiller in RHC 2% can be due to the extra nutrient available to the plant due to increased water holding capacity of soil [36] [41]. Application of biochar to soil enhances the soil physical properties and also increases the nutrient supply to plant [42].…”
Section: The Effect Of Rh and Rhc On Crop Growth And Yield Componentsmentioning
confidence: 99%
“…5). Especially, the latter reflects efforts by China to protect the environment and to restore degraded/polluted land (Zhang et al 2016;Albert and Xu 2014) using biochar (Kong et al 2014;Ahmad et al 2014;Zhang et al 2013). Other countries in this group (e.g.…”
Section: Influence Of Development On Biochar Researchmentioning
confidence: 99%